(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study investigates the effect of camphor oil on Aspergillus parasiticus using the Poisoned Food Technique. Aspergillus parasiticus is a common fungal pathogen known to cause various agricultural and food-related diseases. Camphor oil, derived from the camphor tree, has shown promising antimicrobial properties in previous studies. In this experiment, the Poisoned Food Technique was employed to evaluate the antifungal potential of different concentrations of camphor oil viz., 20%, 40%, 60%, 80% and 100% against Aspergillus parasiticus isolated from okra (Abelmoschus esculentus). Different concentrations of camphor oil were incorporated into the growth medium, and the inhibition of fungal growth was measured. The results indicate that camphor oil exhibits a significant antifungal effect on Aspergillus parasiticus at all concentrations. These findings suggest that camphor oil has potential as a natural alternative to synthetic fungicides in controlling Aspergillus parasiticus and mitigating its detrimental impacts on agriculture and food safety.